CRISPR-Based Gene Editing in Acinetobacter baumannii to Combat Antimicrobial Resistance - Muhammad Junaid; Krit Thirapanmethee; Piyatip Khuntayaporn; Mullika Traidej Chomnawang (MDPI AG, 2023)
Antimicrobial resistance (AMR) poses a significant threat to the health, social, environment, and economic sectors on a global scale and requires serious attention to addressing this issue. Acinetobacter baumannii was given top priority among infectious bacteria because of its extensive resistance to nearly all antibiotic classes and treatment options. Carbapenem-resistant A. baumannii is classified as one of the critical-priority pathogens on the World Health Organization (WHO) priority list of antibiotic-resistant bacteria for effective drug development. Although available genetic manipulation approaches are successful in A. baumannii laboratory strains, they are limited when employed on newly acquired clinical strains since such strains have higher levels of AMR than those used to select them for genetic manipulation. Recently, the CRISPR-Cas (Clustered regularly interspaced short palindromic repeats/CRISPR-associated protein) system has emerged as one of the most effective, efficient, and precise methods of genome editing and offers target-specific gene editing of AMR genes in a specific bacterial strain. CRISPR-based genome editing has been successfully applied in various bacterial strains to combat AMR; however, this strategy has not yet been extensively explored in A. baumannii. This review provides detailed insight into the progress, current scenario, and future potential of CRISPR-Cas usage for AMR-related gene manipulation in A. baumannii.